1981
DOI: 10.1128/aac.19.4.513
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim-rifampin, a new combination agent: efficacy in localized urinary infection and influence on microflora

Abstract: Twenty women with recurrent or persistent urinary tract infections were treated with a fixed combination of trimethoprim-rifampin (TMP-RAM). The site of infection was established by the antibody-coated bacteria test. Sixteen women had upper tract infections (antibody-coated bacteria tests positive); eight were cured, three failed, and five relapsed. All four women with lower tract infections (antibody-coated bacteria tests negative) were cured. Three of five patients with structural abnormalities failed. The 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

1981
1981
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…This combination has also been shown to be effective in women who have had recurrent upper UTI (6). In this study, we found that the overall relapse rate was significantly higher in patients who received 10 days of RIF-TMP than in patients who received 10 days of SMX-TMP, although this difference was not observed in patients with upper UTI.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…This combination has also been shown to be effective in women who have had recurrent upper UTI (6). In this study, we found that the overall relapse rate was significantly higher in patients who received 10 days of RIF-TMP than in patients who received 10 days of SMX-TMP, although this difference was not observed in patients with upper UTI.…”
Section: Discussioncontrasting
confidence: 45%
“…The most common side effect was yeast vaginitis. Nausea was also common with RIF-TMP, but it was considerably less prevalent than that observed by Bourgault et al (6), who treated patients with 1,200 mg of rifampin in one dose. Rifampin is known to cause menstrual disorders in women who take oral contraceptives and may cause increased metabolism of exogenous estrogens (30).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation